Towards a Tool Environment for Model-Based Testing with AsmL - Barnett, Mike; Grieskamp, Wolfgang; Nachmanson, Lev; Schulte, Wolfram; Tillmann, Nikolai; Veanes, Margus (FATES 2003, 2004)
We present work on a tool environment for model-based testing with the Abstract State Machine Language (AsmL). Our environment supports semi-automatic parameter generation, call sequence generation and conformance testing. We outline the usage of the environment by an example, discuss its underlying technologies, and report on some applications conducted in the Microsoft environment.